IMPLEMENTASI ICT DALAM PEMBELAJARAN PAI (STUDI ANALISIS MENGEMAS PEMBELAJARAN PAI BERBASIS ICT DALAM PENDEKATAN SAINTIFIK) - Siti Halidah (Institut Agama Islam Darul Ulum Kandangan, 2020)
ICT (Information and Communication Technology) is a technological device that is used as an alternative method in scientific approach-based PAI (Islamic Education) learning. ICT can be used in all learning for all levels and ages, from formal and non-formal education advantageously. ICT technology provides positive energy in the activities of design learning effectively and efficiently. Beside that, activity in the class is part of important steps learning to reach in the best purpose.